Pelaksanaan Pembelajaran Seni Budaya (Musik) Materi Bernyanyi Berbasis Kurikulum Merdeka - Anisa Ababil; Jagar Lumbantoruan (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine and describe the Implementation of Cultural Arts (Music) Learning Singing Material Based on the Independent Curriculum Class VII B SMP Unp Laboratory Development. This type of research is qualitative, with a descriptive approach. Research instruments are researchers themselves and are assisted by supporting instruments such as stationery, cameras and mobile phones. Data collection techniques are carried out through literature study, observation, interviews and documentation. Data analysis techniques are collecting data, classifying data, clarifying data, analyzing data, describing data and inferring data. The results showed that learning planning has not been fully guided by the teaching modules in the independent curriculum, the impact of these conditions, the learning outcomes of students are still not optimal. Then, at the stage of implementing learning, it has not been carried out optimally because when carrying out learning the teacher is not fully guided by the teaching modules made. Assessments, methods and learning strategies used by teachers have not been implemented in accordance with the stage of cultural arts learning outcomes based on the independent curriculum. Teachers who are too fixated on the material and lack of teacher intervention in the learning process of students Furthermore, at the evaluation stage, a full summative assessment has not been carried out, such as teachers do not do.